2016
DOI: 10.3892/or.2016.4811
|View full text |Cite
|
Sign up to set email alerts
|

HDAC6 promotes cell proliferation and confers resistance to gefitinib in lung adenocarcinoma

Abstract: Histone deacetylases (HDACs) are promising targets for cancer therapy, and first-generation HDAC inhibitors are currently in clinical trials for the treatment of cancer patients. HDAC6, which is a key regulator of many signaling pathways that are linked to cancer, has recently emerged as an attractive target for the treatment of cancer. In the present study, HDAC6 was found to be overexpressed in lung adenocarcinoma cell lines and was negatively correlated with the prognosis of patients with lung adenocarcinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 32 publications
1
35
0
1
Order By: Relevance
“…6). In comparison 36 , observed an increased expression of HDAC6 in lung AdCa and the aberrant expression correlated negatively with patient prognosis. Recently, it has also been reported that HDAC6 suppresses RASSF1A expression 37 .…”
Section: Discussionmentioning
confidence: 81%
“…6). In comparison 36 , observed an increased expression of HDAC6 in lung AdCa and the aberrant expression correlated negatively with patient prognosis. Recently, it has also been reported that HDAC6 suppresses RASSF1A expression 37 .…”
Section: Discussionmentioning
confidence: 81%
“…We used the HDAC3-specific inhibitor RGFP96622, HDAC6-specific inhibitor CAY1060323, and HDAC8-specific inhibitor PCI3405124 to treat expanded NK cells. We found that VPA ≤ 0.5 mM, RGFP966 ≤ 20 μM, CAY10603 ≤ 50 nM and PCI34051 ≤ 0.625 μM did not impair NK cell viability at 24 h (Suppl.…”
Section: Resultsmentioning
confidence: 99%
“…It was found to be upregulated in oral squamous cell carcinoma, 26 ovarian carcinoma, 27,28 and primary acute myeloid leukemia 29 relative to nonmalignant controls. Preclinical studies have demonstrated that HDAC6 inhibitors display antitumor activity when used either alone or in combination with other agents to treat multiple myeloma, 30,31 B-cell lymphoma, 24,32 breast cancer, 33,34 lung cancer, 35,36 and melanoma. 37,38 At present, HDAC6-selective inhibitors are in clinical trials to treat several solid tumor types, multiple myeloma, and lymphoma (registered at www.clinicaltrials.…”
Section: Introductionmentioning
confidence: 99%